Compost science for gardeners : simple methods for nutrient rich soil - Pavlis, Robert (New Society Publishers, 2023)
"Compost Science for Gardeners demystifies the full range of composting methods and helps readers determine or select the best technique for their situation. This comprehensive, plain-language, science-based book covers everything from the inputs required to the beneficial impacts on the environment and soil health."--